Against a Continental Threat: Transnational Anti-Communist Networks of the Chilean Right Wing in the 1950s. Issue 3 (31st January 2019) - Casals, Marcelo
Abstract: Drawing on minutes, publications, diplomatic documents and the written press, I explore the transnational networks of the Chilean right wing within Latin America in the 1950s, especially around the four Congresses against Soviet Intervention in Latin America held in Mexico City, Rio de Janeiro, Lima and Antigua between 1954 and 1958. I argue that the Chilean right wing's participation in those networks alongside other Latin American like-minded actors was based on both its long local experience in fighting communism and its attachment to Cold War anti-communism. In these transnational spaces, some Chilean right-wingers gained recognition and prestige, as was the case with the conservative leader Sergio Fernández Larraín, largely thanks to his systematic denunciation of supposed Soviet penetration in the Movimiento Nacionalista Revolucionario (MNR), then the ruling party in Bolivia. Spanish abstract: A partir de minutas, publicaciones, documentos diplomáticos y prensa escrita, exploro las redes transnacionales de la derecha chilena en América Latina en los años 1950s, especialmente alrededor de los cuatro Congresos contra la Intervención Soviética en América Latina llevados a cabo en la Ciudad de México, Río de Janeiro, Lima y Antigua entre 1954 y 1958. Argumento que la participación de la derecha chilena en esas redes junto a otros actores latinoamericanos afines se basó tanto en su experiencia local de larga data en su lucha contra el comunismo como en su conexión con el anticomunismo de la Guerra Fría. En estos espacios tradicionales, algunos derechistas chilenos obtuvieron reconocimiento y prestigio, como fue el caso del líder conservador Sergio Fernández Larraín, en gran parte gracias a su sistemática denuncia de la supuesta penetración soviética en el Movimiento Nacionalista Revolucionario (MNR), entonces en el poder en Bolivia. Portuguese abstract: Com base em atas de reuniões, publicações, documentos diplomáticos e da imprensa escrita, eu exploro as redes transnacionais da direita do Chile na América Latina dos anos 1950s, focando em particular nos quatro Congressos Contra a Intervenção Soviética na América Latina realizados na Cidade do México, Rio de Janeiro, Lima e Antígua entre 1954 e 1958. Argumento também que a integração da direita Chilena a estas redes, conjuntamente com outros agentes Latino Americanos semelhantes, foi devido à experiência da mesma em lutar contra o comunismo e sua ligação ao anticomunismo da Guerra Fria. Nestes espaços transnacionais, alguns membros da direita ganharam prestígio e reconhecimento, como foi o caso do líder conservador Sergio Fernández Larraín, em grande parte devido à denúncia sistemática da suposta penetração Soviética no Movimento Nacionalista Revolucionário (MNR), nesse momento o partido governista da Bolívia.